Smart offshore structure for reliability prediction process - Nwankwo, Cosmas Chidozie (Cranfield University, 2013)
A review of the developments within the field of structural reliability theory shows that some gaps still exist in the reliability prediction process and hence there is an urgent desire for improvements such that the estimated structural reliability will be capable of expressing a physical property of the given structure. The current reliability prediction process involves the continuous estimation and use of reliability index as a way of estimating the safety of any given structure. The reliability index β depends on the Probability Density Function (PDF) distribution for the wave force and the corresponding PDF of resistance from respective structural members of the given structure. The PDF for the applied wave force will depend on the PDF of water depth, wave angular velocity and wave direction hence the reliability index as currently practiced is a statistical way of managing uncertainties based on a general probabilistic model. This research on Smart Offshore Structure for Reliability Prediction has proposed the design of a measurement based reliability prediction process as a way of closing the gap on structural reliability prediction process. Structural deflection and damping are some of the measurable properties of an offshore structure and this study aims at suggesting the use of these measurable properties for improvements in structural reliability prediction process. A design case study has shown that a typical offshore structure can deflect to a range of only a few fractions of a millimetre. This implies that if we have a way of monitoring this level of deflection, we could use the results from such measurement for the detection of a structural member failure. This advocated concept is based on the hypothesis that if the original dynamic characteristics of a structure is known, that measurement based modified dynamic properties can be used to determine the onset of failure or failure propagation of the given structure. This technology could reveal the location and magnitude of internal cracks or corrosion effects on any given structure which currently is outside the current probability based approach. A simple economic analysis shows that the recommended process shows a positive net present value and that some $74mln is the Value of Information for any life extension technology that could reveal the possibility of extending the life of a given 10,000bopd production platform from 2025 to 2028.
Keywords: Reliability; HUMS; Business controls; Risk; uncertainty; Offshore Structures; structural reliability; technology analogue; Smart process; real time data acquisition; dynamic reservoir simulation updating